Association Between Constraints Encountered by the Farmers in Adoption of Drip Irrigation System and their Selected Independent Variables - Krishna Yadav, J. P. Yadav , Seema Yadav and Kumari Asha (Indian Journal of Extension Education, 2018)
Rajasthan has largest geographical area having only 1per cent water resources of country. Due to arid and semi-aridclimate i.e. negative moisture index, poor soil quality and traditional agriculture practices, the food security, nutritionalsecurity, Irrigation scenario of Rajasthan is characterized by erratic or /sporadic/scanty rainfall, dwindling ground waterresources increasing alternative demand of municipal and industrial sector that means less water available for agriculture.In Rajasthan, Water is the most precious natural resource, vitally important for agricultural development and for day-todayliving..In the changing agricultural scenario world over and shift towards precision farming, drip irrigation happens tobe the technology capable of providing more efficient utilization of water. The study was conducted in eight selectedGram Panchayat of Jhotwara Panchayat Samiti of Jaipur District of Rajasthan. Two villages were selected from eachselected Gram Panchayat of Jhotwara Panchayat Samiti having maximum number of drip irrigation sets. Thus, sixteenvillages were selected purposively. Ninety six farmers were selected from sixteen selected villages on the basis ofproportional allocation to the size of sample. The seven variables viz. socio-economic status, caste, occupation, educationlevel, size of land holding, age and extension participation were identified as the important variables to measure theassociation between the constraints encountered by the farmers in adoption of drip irrigation system and selectedindependent variables and following results were found. It was observed that 'socio-economic status', 'caste', and'education level' were found to be negative and significantly where as 'occupation' and 'extension participation' werepositive and significantly associated with the constraints encountered by the farmers in adoption of drip irrigation systemwhile the variables like 'size of land holding' was negative and 'age' was positive but both were non-significantlyassociated with the constraints encountered by the farmers in adoption of drip irrigation system.